Perencanaan dan Optimasi Sistem Distribusi Air Bersih di Kecamatan Babahrot Berdasarkan Proyeksi Kebutuhan Masyarakat - M. Arif Munanda; Nia Arfina Foci; Muhamad Yasin; Rama Dani Eka Putra; Tessa Zulenia Fitri (JURNAL RISET DAN APLIKASI TEKNIK INDUSTRI, 2026)
community, especially in areas that are not fully covered by PDAM services. This study aims to analyze the potential of the Pante Rakyat Reservoir as a raw water source to support the clean water supply system in Babahrot District, Southwest Aceh Regency. The method used involves analyzing clean water needs based on existing population data, population growth projections for the next 5 to 25 years, and the reservoir's capacity. The results show that, out of a total of 12,520 people, approximately 4% of the population lacks access to clean water. Assuming a population growth rate of 3% per year, the estimated need for clean water is projected to reach 954,000 liters per day, or approximately 11.04 liters per second, and increase to 14.49 liters per second over the next five years. The water distribution plan is supported by the design of a 0.24-meter-diameter intake pipe system. The conclusion of this study suggests that the Pante Rakyat Reservoir has significant potential as a long-term raw water source and is worthy of optimization to meet the clean water needs of the Babahrot District community.